2019
DOI: 10.1038/s41598-019-39489-4
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin impairs acetyl-coenzyme A metabolism in redox-compromised yeast cells

Abstract: Aspirin is a widely used anti-inflammatory and antithrombotic drug also known in recent years for its promising chemopreventive antineoplastic properties, thought to be mediated in part by its ability to induce apoptotic cell death. However, the full range of mechanisms underlying aspirin’s cancer-preventive properties is still elusive. In this study, we observed that aspirin impaired both the synthesis and transport of acetyl-coenzyme A (acetyl-CoA) into the mitochondria of manganese superoxide dismutase (MnS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…In agreement with previous experiments, it has been shown that ASA could increase the synthesis of different PGs, such as PGE 2 and PGI (Du, Pan, Duan, Yang, & Ge, 2016). In contrast, Farrugia et al showed that the suppression of acetyl‐CoA metabolic pathways after treatment with ASA could abort the normal synthesis of FF (Farrugia et al, 2019). Although 0.5 mM ASA was not able to make any significant reduction on PGE 2 levels while dramatically decreased (1,000‐fold) E 2 levels and ER protein, which showed a great significant role in early antral to large antral progression, estradiol production and ovulation (Emmen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous experiments, it has been shown that ASA could increase the synthesis of different PGs, such as PGE 2 and PGI (Du, Pan, Duan, Yang, & Ge, 2016). In contrast, Farrugia et al showed that the suppression of acetyl‐CoA metabolic pathways after treatment with ASA could abort the normal synthesis of FF (Farrugia et al, 2019). Although 0.5 mM ASA was not able to make any significant reduction on PGE 2 levels while dramatically decreased (1,000‐fold) E 2 levels and ER protein, which showed a great significant role in early antral to large antral progression, estradiol production and ovulation (Emmen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…They inhibits EP300 and protein acetylations and can activate autophagy [5][6][7]. In MnSOD-deficient yeast cells aspirin/salicylate starve the mitochondria of acetyl-CoA, inducing cell death [8]. In WT yeast cells salicylate can alter the balance between cell quiescence, death and proliferation as a function of metabolic signals [9].…”
Section: Introductionmentioning
confidence: 99%
“…aspirin impairs acetyl-coenzyme A metabolism and causes mitochondrial damage, resulting in yeast cell death [5]. However, the molecular mechanism underlying the antifungal effect of aspirin is still unclear.…”
mentioning
confidence: 99%